2016
DOI: 10.1038/bjc.2016.252
|View full text |Cite
|
Sign up to set email alerts
|

Role of histological regression grade after two neoadjuvant approaches with or without radiotherapy in locally advanced gastric cancer

Abstract: Background:The degree of histopathological response after neoadjuvant therapy in locally advanced gastric cancer (GC) is a key determinant of patients' long-term outcome. We aimed to assess the pattern of histopathological regression after two neoadjuvant approaches and its impact on survival times.Methods:Regression grade of the primary tumour (Becker criteria) and the degree of nodal response by a 4-point scale (grades A–D) were assessed. Grade A—true negative lymph nodes (LNs); grade B and C—infiltrated LNs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
41
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 27 publications
9
41
0
2
Order By: Relevance
“…For the Mandard TRG, some studies supported that TRG 1-2 should be classified into responders, which was in accordance with our study [7,18,19], while some others believed that TRG 1-3 was better in distinguishing the prognosis [20][21][22]. For the Becker TRG, there were studies supporting the same consequence as ours [1,[23][24][25], while others suggested TRG 1-2 owned a better prognosis than TRG 3 [9,10,26,27]. This discrepancy might partly derive from the differences in subjective evaluations of the pathologists.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…For the Mandard TRG, some studies supported that TRG 1-2 should be classified into responders, which was in accordance with our study [7,18,19], while some others believed that TRG 1-3 was better in distinguishing the prognosis [20][21][22]. For the Becker TRG, there were studies supporting the same consequence as ours [1,[23][24][25], while others suggested TRG 1-2 owned a better prognosis than TRG 3 [9,10,26,27]. This discrepancy might partly derive from the differences in subjective evaluations of the pathologists.…”
Section: Discussionsupporting
confidence: 90%
“…Tumor regression grade (TRG) is a system to assess the quantity of residual tumor, which could provide extra information to evaluate the curative effects and prognosis [1,4]. Nevertheless, there are various systems without a consensus [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Gastric cancer is an adenocarcinoma, and a radiotherapy dose of 45-50.4 Gy can lead to serious adverse reactions. 20 This has led to a strong requirement for the development of radiotherapy technology, particularly as related to precision, delineating the radiotherapy target area, and the formulation and implementation of a radiotherapy plan. With radiotherapy for gastric cancer, uncertain factors such as changes in the body position during radiotherapy, the influence of diaphragmatic respiratory movements, and the change in gastric volume and gastrointestinal motility should be considered.…”
Section: Radiotherapymentioning
confidence: 99%
“…In addition to stratification, the combination of TRG and lymph node stage was also used to predict the survival [ 2 , 3 , 18 , 26 ]. Based on the MAGIC trial, Smyth et al [ 3 ] found that patients in TRG 3-5 and node positive group owned worse overall survival than others, while patients with TRG 1-2 and node negative were the best, which is consistent with our result.…”
Section: Discussionmentioning
confidence: 99%
“…Another paper from the UK showed similar outcome, while they suggested the boundary should be TRG 1-3 vs. 4-5 [ 18 ]. Holscher et al [ 26 ] and Martin-Romano et al [ 2 ] also considered the responders with node negative owned better prognosis when using the TRG of proportion.…”
Section: Discussionmentioning
confidence: 99%